Pembelajaran EDP-Problem Solving Project untuk Melatih Siswa Meningkatkan Keterampilan Berpikir Kritis dan Penyelesaian Masalah - Setiawan, Dani (Jurnal Didaktika Pendidikan Dasar, 2020)
Indonesian students still need to strengthen their ability to integrate information, draw conclusions, and introduce their knowledge to other things. Indonesian students are still weak in answering questions with a level of reasoning. So the purpose of this study is to find out the critical thinking skills and problem-solving of students in class VII-A SMPN 1 Bulakamba academic year 2018/2019 can be improved through learning EDP-Problem Solving Project. EDP-Problem Solving Project facilitates students to implement the engineering design process in conducting problem-solving projects. EDP-Problem Solving Project learning activities consist of stages (1) ask (formulate questions), (2) imagine, (3) plan (plan), (4) creat (make), (5) test (try out), (6) analyze (analyze), (7) conclude (conclude), (8) communicate (communicate), and (9) improve (develop). The study was conducted with a class action research procedure. Data on critical thinking skills and problem-solving are analyzed descriptively. The results showed that critical thinking skills and problem-solving for students of class VII-A SMPN 1 Bulakamba in the 2018/2019 academic year could be improved through learning the EDP-Problem Solving Project.